Disparities exist between National food group recommendations and the dietary intakes of women - MacDonald-Wicks Lesley K (BMC Women's Health, 2011)
Abstract Background Preconception and pregnancy dietary intakes can influence the health of future generations. In this study we compared the food intakes of reproductive-aged women by pregnancy status, to current Australian recommendations. Methods Data are from the Australian Longitudinal Study on Women's Health, younger cohort aged 25-30 years in 2003, with self-reported status as pregnant (n = 606), trying to conceive (n = 454), given birth in the last 12 months (n = 829) or other (n = 5597). Diet was assessed using a validated 74-item food frequency questionnaire. Food group servings and nutrient intakes were compared to the Australian Guide to Healthy Eating (AGHE) and Australian Nutrient Reference Values (NRVs). Results No women met all AGHE food group recommendations. Highest adherence rates [mean (95% CI) servings/day] were for meat [85%, 1.9(1.8-1.9)], fruit [44%, 2.1(2.1-2.2)] and dairy [35%, 1.8(1.8-1.9)], with < 14% meeting remaining recommendations. Women who achieved NRVs (folate, iron, calcium, zinc, fibre) for pregnancy, breastfeeding and adult life stages were 1.5%, 3.3% and 13.7%, respectively. Compared to AGHE, women consumed more servings of fruit (4.9 vs 4.0;P = 0.034) and dairy (3.4 vs 2.0;P = 0.006) to achieve pregnancy NRVs; more dairy (2.9 vs 2.0;P = 0.001), less fruit (3.9 vs 5.0;P < .001) and vegetables (3.4 vs 7.0;P < .001) to achieve breastfeeding NRVs; more fruit (3.6 vs 3.0;P < .001), dairy (2.5 vs 2.0;P < .001), meat (1.8 vs 1.5;P = 0.015), less vegetables (3.6 vs 5.0;P < .001) to achieve adult NRVs. Conclusions The AGHE does not align with contemporary diets of Australian women or enable them to meet all NRVs. Current tools to guide food consumption by women during pregnancy require revision.